(untitled) (Revista de Ciências Agroveterinárias, 2019)
The objective of this study was to compare the effect of different training systems on the vegetative-productive efficiency and chemical composition of the Cabernet Sauvignon grapevine cultivated in southern Brazil. The experiment was conducted in 2011, 2012 and 2013 vintages under an experimental vineyard located in the municipality of Lages, Santa Catarina. The vineyard was implanted in 2007 with crown variety grafted on the Paulsen 1103 rootstock, while having a spacing of 3.0 m between rows and 1.2 m between plants. The treatments consisted of four conduction systems: double curtain ("Geneva Double Cortine" - GDC), discontinuous trellis, simple curtain, and VSP. The variables were subjected to analysis of variance (ANOVA) and compared by Tukey test with a 5% probability of error. It was observed that the training systems influence the vegetative-productive efficiency and chemical composition of the berries of the Cabernet Sauvignon grapevine. GDC systems and discontinuous grapes increase productivity, as well as provide a better vegetative-productive balance and result in grapes with lower acidity.